6,6′-[(1E,1′E)-Oxybis(4,1-phenylene)bis(azanylylidene)bis(methanylylidene)]bis(2-methylphenol): supramolecular assemblies in two dimensions mediated by weak C—H...N, C—H...O and C—H...π interactions - Md. Azharul Arafath; Huey Chong Kwong; Farook Adam; Mohd. R. Razali (Acta Crystallographica Section E: Crystallographic Communications, 2018)
The title compound, C28H24N2O3, is a flexible Schiff base, having a dihedral angle of 59.53 (5)° between the mean planes of two phenyl rings bounded in the centre by a single O atom. The dihedral angles between the mean planes of the phenyl rings bonded to the central O atom and the mean planes of the terminal methylphenol rings are 31.47 (6) and 36.03 (5)°, respectively. The sp2-hybridized character of the azanylylidene groups is confirmed by their bond lengths and bond angles. In the crystal, molecules are linked into centrosymmetric dimers by weak C—H...N interactions and connected into dimeric chains through weak C—H...O interactions. These chains are interconnected into a two-dimensional network parallel to (1\overline{2}1) via weak C—H...π interactions.